Significance of differences between procedure-process-activity for university institutional self - Romero, Hernando A. (2012)
Refers to a broad reflection, tobe clear about the difference in meaning between activity, procedure, process, social activity, processsocial and personal is very important in the field ofinstitutional self because if you do not recognize their differences, can not properly referwhat is meant by academic and differences in the educational process.